Challenges and perspectives for catalysis in production of diesel from biomass. Issue 4 (July 2011) - Madsen, Anders Theilgaard; Søøndergaard, Helle; Fehrmann, Rasmus; Riisager, Anders
The production of biofuels is expected to increase in the future due to environmental concerns, accelerating oil prices and the desire to achieve independence from mineral oil sources. Of the proposed methods for diesel production from biomass, the esterification and transesterification of plant oils or waste fats with methanol is the most prominent and has been applied industrially for a decade. Homogeneous acid and base catalysis is normally used, but solid acids, solid bases, ionic liquids and lipases are being developed as replacements. Hydrodeoxygenation of vegetable oils has likewise been commercialized. Diesel from biomass may also be produced by catalytic upgrading of bio-oils from flash pyrolysis, by aqueous-phase reforming of carbohydrates into non- or mono-functionalized hydrocarbons via consecutive reduction-condensation reactions, or by gasification of biomass to synthesis gas of CO and H2 and liquefaction to alkanes via Fischer––Tropsch synthesis. Here, the current challenges and perspectives regarding catalysis and raw materials for diesel production from biomass are surveyed.